Airway infection with Nontypeable Haemophilus influenzae is more rapidly eradicated in vitamin D deficient mice. Issue 187 (March 2019) - Serré, Jef; Mathyssen, Carolien; Ajime, Tom Tanjeko; Korf, Hannelie; Maes, Karen; Heulens, Nele; Gysemans, Conny; Mathieu, Chantal; Vanaudenaerde, Bart; Janssens, Wim; Gayan-Ramirez, Ghislaine
Highlights: Enhanced bacterial clearance in vitamin D deficient mice infected with NTHi. Cigarette smoke inhibited phagocytosis and oxidative burst, but had no effect on bacterial clearance. Faster resolution of local lung inflammation in vitamin D deficient mice. Upregulation of CRAMP mRNA as possible mechanism for faster eradication in vitamin D deficient mice. Misbalance of the protease and anti-protease homeostasis towards proteolysis in NTHi infected vitamin D deficient mice. Abstract: Chronic obstructive pulmonary disease (COPD), which is characterized by an excessive inflammatory response of the airways, is often complicated by exacerbations. Vitamin D deficiency has been associated with an increased risk for COPD and may predispose COPD patients to a higher exacerbation rate, particularly during smoking. In the current study, we investigated the effect of vitamin D deficiency and cigarette smoke (CS)-exposure on lung inflammation and bacterial clearance after an acute infection with Nontypeable Haemophilus influenzae (NTHi). Vitamin D deficient or sufficient mice were exposed to nose-only CS or ambient air for 6 weeks and oropharyngeally instilled with 10 6 NTHi. Residual viable NTHi were measured at different time points post-infection. Mechanisms of bacterial clearance (e.g. phagocytosis, pattern recognition receptors, antimicrobial peptides, surfactant proteins and mucin) and lung remodeling (e.g. metalloproteinases, MMP's) were assessed. Although smoking resulted in reduced phagocytosis capacity of macrophages and neutrophils, bacterial clearance was similar to control mice. By contrast and independent of smoking, bacterial clearance was significantly accelerated in vitamin D deficient mice already from 24 h post-infection (p = 0.0087). This faster and complete eradication was associated with a more rapid resolution of cytokines and neutrophils 72 h post-infection and dominated by an upregulation of cathelicidin-related antimicrobial peptide (CRAMP) mRNA during infection (p = 0.026). However, vitamin D deficiency also resulted in more MMP12 protein in broncho-alveolar lavage and a shift in mRNA expression of MMP12/TIMP1 (p = 0.038) and MMP9/TIMP1 (p = 0.024) ratio towards more protease activity. Overall, vitamin D deficient mice resolved NTHi infection faster with a faster resolution of local lung inflammation, possibly through upregulation of CRAMP. This was associated with a disruption of the protease/anti-protease balance, which may potentially scale towards a higher extracellular matrix breakdown.